Ischemic Risk in Patients with Zero Coronary Artery Calcium Undergoing Stress PET/CT Testing - Jeffrey L. Anderson; Leslie K. Iverson; Daniel L. Bride; Stacey Knight; Raymond O. McCubrey; Viet T. Le; Mohanad Dakhakhni; Steve M. Mason; Kirk U. Knowlton (Journal of Clinical Medicine, 2026)
Background: The absence of coronary artery calcium (CAC = 0) on computed tomography (CT) portends a low but not zero coronary risk. However, the frequency and prognostic significance of non-calcified plaques in CAC = 0 patients are incompletely defined, and non-coronary artery disease (CAD) causes of coronary risk have been proposed. We sought to define the ischemic burden, CAD status, and outcomes of CAC = 0 patients. Methods: The Intermountain electronic medical records were searched for CAC = 0 patients undergoing stress positron emission tomography (PET)/CT between January 2016 and July 2022. We defined definite PET abnormality as ischemic burden (IB) ≥ 10%. Patients were followed for angiographic findings, interventions, and major adverse cardiovascular events (MACE) over 3.1 ± 1.3 years. Results: Of 22,542 PET/CT studies in primary prevention patients, 5054 (22.4%) had CAC = 0. Of these, 59 (1.2%) had IB ≥ 10% on PET. Selective coronary angiography was performed within 90 days in 25 (42%) of IB ≥ 10% patients. Severe CAD was present in 11, but findings were not explained by CAD in 14. Revascularization was indicated in 10 (16.9%) of 59 with IB ≥ 10% vs. 0.04% of IB = 0% (p < 0.0001); 3-year outcomes also were lower with IB = 0%. Conclusions: In this large series of stress PET/CT study data, IB ≥ 10% in patients with CAC = 0 was rare. Most positive PET tests were not explained by obstructive CAD. While CAC does not perfectly predict an absence of coronary ischemia or obstructive CAD, it is a strong marker of prognosis. Here, we show that IB by PET supplements CAC score to importantly refine risk assessment.